Annotated checklist and key to species of Gryllotalpa (Orthoptera: Gryllotalpidae) from the Oriental region - Tan, Ming Kai (Zootaxa, 2016)
The cosmopolitan Gryllotalpa mole cricket is the most speciose genus (70 species) in the family Gryllotalpidae. The taxonomy and diversity of Oriental species are not well understood. A species list with 26 species is presented here. An artificial key is also presented aimed to help with species identification, new species discovery and future taxonomic revision in the biodiverse Oriental region.